Functional current collector with low residual stress and preparation method and application thereof

By injecting nitrogen ions into the functional current collector and controlling the nitrogen ion concentration to form compounds such as copper nitride, the stress deformation caused by residual stress in the functional current collector and the metal conductive layer fall off are solved, and the cycle life and safety performance of lithium batteries are improved.

CN119650714AActive Publication Date: 2025-03-18YANGZHOU NANOPORE INNOVATIVE MATERIALS TECH LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510180275.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-19
Publication Date
2025-03-18
Estimated Expiration
2045-02-19

AI Technical Summary

Technical Problem

When the deposition rate of the metal conductive layer in the functional current collector is too fast on the surface of the polymer polymer layer, residual stress will be generated, resulting in stress deformation of the functional current collector and falling off the metal conductive layer, affecting the cycle life and safety performance of the lithium battery.

Method used

By injecting nitrogen ions into the functional current collector and controlling the proportion of nitrogen ion concentration in the junction area between the polymer layer and the metal layer, compounds such as copper nitride are formed to enhance the stability of the metal layer, adjust the residual stress in the metal layer, and change the internal structure and stress distribution of the polymer layer to reduce the overall residual stress of the functional current collector.

Benefits of technology

Effectively reduce residual stress in the functional current collector, improve the binding stability of the metal layer on the surface of the polymer layer, extend the cycle life of the lithium battery and improve safety performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention specifically discloses a functional current collector with low residual stress and a preparation method and application thereof. The invention discloses a functional current collector with low residual stress. The functional current collector comprises two metal layers and a polymer layer arranged between the two metal layers, wherein the range from the surface of the polymer layer to the 2-3 [mu] m far away from the metal layer in the polymer layer is marked as a region A, the range from the surface of the metal layer close to the polymer layer to the 100 nm far away from the polymer layer in the metal layer is marked as a region B, and the region A and the region B are junction regions of the polymer layer and the metal layer; the functional current collector contains nitrogen ions, and the concentration of the nitrogen ions in the junction region of the polymer layer and the metal layer accounts for more than 80% of the total concentration of the nitrogen ions in the functional current collector. The method has the advantages that the residual stress of the functional current collector is weakened, the stability of the functional current collector is improved, the cycle life of the battery is prolonged, and the safety performance is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium batteries, and in particular to a functional current collector with low residual stress, and a preparation method and application thereof. Background Art

[0002] With the rapid development of new energy technology and electronic technology, batteries are gradually becoming a research hotspot. How to improve the cycle life, safety performance, energy density, etc. of batteries has become a top priority. As an important part of the battery structure, the current collector can collect the current generated by the active materials in the battery to form a larger external current output. The quality of the current collector performance will directly affect the cycle life, safety performance, energy density, etc. of the battery.

[0003] At present, the positive and negative electrodes in lithium batteries and sodium batteries mostly use aluminum foil and copper foil as current collectors. This type of current collector has a high cost, which is not conducive to controlling battery costs and improving energy density. Functional current collectors have obvious advantages over traditional foil current collectors. Functional current collectors are usually a "sandwich" structure, with a polymer layer as the inner layer and metal conductive layers deposited on the polymer layer on both sides; the metal conductive layer on the surface of the functional current collector is thinner and the polymer layer on the inner layer is lighter, which can well reduce the overall weight of the functional current collector, thereby helping to improve the energy density of lithium batteries; at the same time, the thinner metal conductive layer on the surface of the functional current collector is easier to disconnect than the traditional foil current collector when the lithium battery has thermal runaway, thereby isolating the connection between the active material and the current collector, preventing the lithium battery from continuing to have thermal runaway, and helping to improve the safety performance of lithium batteries.

[0004] Although functional current collectors have the advantages of low cost and light weight, it is found in actual applications that when the metal conductive layer in the functional current collector is deposited on the surface of the polymer polymer layer at a rate too fast, residual stress will be generated, which will lead to stress deformation of the functional current collector and increase the risk of the metal conductive layer falling off the polymer polymer layer, which will be detrimental to improving the battery cycle life and safety performance. Summary of the invention

[0005] In order to reduce the residual stress of the functional current collector and improve the stability of the functional current collector to improve the cycle life and safety performance of the battery, the present application provides a functional current collector with low residual stress and a preparation method and application thereof.

[0006] In a first aspect, the present application provides a functional current collector with low residual stress, which adopts the following technical solution: A functional current collector with low residual stress, the functional current collector comprising two metal layers and a polymer layer disposed between the two metal layers; The range from the surface of the polymer layer to the 2-3 μm away from the metal layer in the polymer layer is recorded as region A, and the range from the surface of the metal layer close to the polymer layer to the 100 nm away from the polymer layer in the metal layer is recorded as region B, and the region A and the region B are the boundary regions between the polymer layer and the metal layer; The functional current collector contains nitrogen ions, and the nitrogen ion concentration in the interface area between the polymer layer and the metal layer accounts for more than 80% of the total nitrogen ion concentration in the functional current collector.

[0007] By injecting nitrogen ions into the functional current collector and controlling the concentration ratio of nitrogen ions in the interface between the polymer layer and the metal layer, first, on the one hand, the nitrogen ions injected into the functional current collector can form a large amount of copper nitride and other compounds in the interface, which can act as a reinforcing agent and form a strong bond with the copper layer to enhance the stability and durability of the metal layer; on the other hand, the production of copper nitride can also improve the structure of the interface between the metal layer and the polymer layer, making the part of the interface located in the metal layer more dense and uniform, thereby reducing the residual stress caused by the uneven structure at the interface between the polymer layer and the metal layer, changing the crystal structure and mechanical properties of the functional current collector, thereby reducing the residual stress and improving the bonding stability of the metal layer on the surface of the polymer layer. Second, after the nitrogen ions are injected into the metal layer in the functional current collector, defects and dislocations will be generated in the metal layer, which can provide a stress release path, thereby adjusting the residual stress in the metal layer to a lower level. Third, some of the nitrogen ions injected into the functional current collector will also penetrate into the polymer layer, and collide and interact with the polymer in the polymer layer, resulting in certain energy transfer and damage, which will lead to the breakage, rearrangement and cross-linking of the molecular chain, thereby changing the internal structure and stress distribution of the material, and thus reducing the overall residual stress of the functional current collector. Based on this, the use of low residual stress functional current collectors in lithium batteries helps to improve the cycle life and safety performance of lithium batteries.

[0008] Preferably, the polymer layer has a thickness of 4-6 μm.

[0009] Preferably, the thickness of any one of the metal layers is 1-2 μm.

[0010] By controlling the thickness of the polymer layer and the metal layer, the thickness of the metal layer is controlled within an appropriate range, and the amount of material used is reduced while ensuring that the current collector has sufficient conductivity, which helps to improve the energy density of the lithium battery. In addition, controlling the thickness of the polymer layer within an appropriate range can effectively prevent and control internal short circuits in the battery, further enhance the insulation of the polymer layer, and avoid safety hazards during battery use.

[0011] Preferably, the polymer layer includes at least one of a polypropylene (PP) film, a polyetheretherketone (PEEK) film, a polyphenylene sulfide (PPS) film, a polyethylene naphthalate (PEN) film, and a polyimide (PI) film.

[0012] Preferably, the metal layer includes any one of copper foil and aluminum foil.

[0013] In a second aspect, the present application provides a method for preparing a functional current collector with low residual stress, using the following technical solution: A method for preparing a functional current collector with low residual stress comprises the following steps: S1, compounding the metal layer on the two surfaces of the polymer layer to obtain a finished current collector, placing the finished current collector in a vacuum atmosphere, and injecting nitrogen ion beams into the surfaces of the two metal layers of the finished current collector to obtain a pretreated current collector; S2, after the injection operation is completed, the pre-treated current collector is subjected to heat preservation treatment and then cooled to obtain the functional current collector.

[0014] Preferably, the pressure in the vacuum atmosphere in S1 is 6×10 -4 -2×10 -3 Pa.

[0015] The nitrogen ion implantation operation is performed in the vacuum atmosphere, which can ensure the high-speed movement of electrons and ions, thereby achieving the purpose of processing the workpiece and avoiding the speed attenuation of the electron beam and the ion beam, so as to ensure the processing effect and processing quality.

[0016] Preferably, in S1, the metal layer is prepared by magnetron sputtering, electron beam evaporation or laser pulse deposition.

[0017] Preferably, during the implantation operation of S1, the implantation energy of the nitrogen ion beam is 50-150 keV, the ion beam current intensity of the nitrogen ion beam is 5-20 mA, and the implantation dose of the nitrogen ion beam is 5×10 16 -5×10 17 Ions / cm 2 .

[0018] By controlling the injection energy of the nitrogen ion beam, the penetration depth of the nitrogen ions in the functional current collector can be adjusted so that the nitrogen ions can be mainly concentrated in the interface area between the polymer layer and the metal layer to reduce the residual stress of the metal layer and improve the stability of the metal layer on the surface of the polymer layer. When the injection energy is too low, the nitrogen ions may only be distributed in the shallow surface of the functional current collector and cannot effectively affect the internal residual stress, resulting in an insignificant effect of eliminating the residual stress in the functional current collector. If the injection energy is too high, the internal structure of the functional current collector may be excessively damaged, or even the original performance of the functional current collector may be changed. Although the residual stress can be eliminated to a certain extent, new performance problems will arise.

[0019] By controlling the intensity of the ion beam of the nitrogen ion beam, the number of nitrogen ions injected into the functional current collector per unit time can be adjusted to produce a sufficient number of nitrides and dislocations, defects, etc. to eliminate the residual stress in the functional current collector. An excessively high ion beam intensity means that a higher number of nitrogen ions are injected into the functional current collector per unit time, which can improve the processing efficiency, but it can also cause problems such as local overheating and surface sputtering, affecting the surface quality and performance uniformity of the functional current collector; accordingly, a weak ion beam intensity leads to a lower processing efficiency, and a longer processing time may be required to achieve the desired residual stress elimination effect.

[0020] By controlling the injection dose of the nitrogen ion beam, the interaction between the nitrogen ions and the metal layer and the polymer layer can be adjusted, and the structure and performance of the interface area between the polymer layer and the metal layer can be changed to reduce the residual stress in the functional current collector. When the injection dose is too low, the interaction between the nitrogen ions and the atoms inside the functional current collector is insufficient, and it is difficult to fully change the structure and performance of the interface area, and the residual stress cannot be effectively eliminated; when the injection dose is too high, it may cause serious distortion of the material lattice in the functional current collector, a large number of defects, and even the formation of new phases. Although the residual stress can be eliminated, it will also cause adverse changes in other properties of the material such as hardness and toughness, which is not conducive to improving the comprehensive performance of the functional current collector.

[0021] Preferably, in S2, the holding temperature is 80-90°C, the holding time is 3-5 min, and the cooling rate is 1-3°C / min, until cooling to 20-25°C.

[0022] By controlling the insulation temperature and insulation time in S2, the nitrogen ions are promoted to better combine and migrate with the internal structure of the material, and stress elimination and structural stability are promoted without adversely affecting other properties of the functional current collector.

[0023] In a third aspect, the present application provides a pole piece, which adopts the following technical solution: A pole piece comprises the functional current collector as described above or the functional current collector prepared by the method as described above and an electrode active material located on the functional current collector.

[0024] In a fourth aspect, the present application provides a lithium battery cell, which adopts the following technical solution: A lithium battery cell comprises the pole piece as described above.

[0025] In a fifth aspect, the present application provides a battery pack, which adopts the following technical solution: A battery pack comprises the lithium battery cell as described above.

[0026] In a sixth aspect, the present application provides an electrical device, which adopts the following technical solution: An electrical device comprises the lithium battery cell or the battery pack as described above.

[0027] In summary, this application has the following beneficial effects: Since in the present application nitrogen ions are injected into the functional current collector and the concentration of nitrogen ions in the interface between the polymer layer and the metal layer is controlled to account for more than 80% of the total concentration of nitrogen ions injected into the current collector, firstly, not only can compounds such as copper nitride be formed in the interface area as a reinforcing agent to enhance the stability of the metal layer, but also the presence of copper nitride can improve the structural uniformity and density at the interface area, and reduce the residual stress caused by structural unevenness in the interface area; secondly, the nitrogen ions injected into the metal layer can produce dislocations and defects in the metal layer, providing a release path for stress release in the metal layer, thereby reducing the residual stress level in the metal layer, which helps to reduce the overall residual stress of the functional current collector; thirdly, some of the nitrogen ions injected into the current collector will also penetrate into the polymer layer, resulting in the breakage, rearrangement and cross-linking of the polymer molecular chains, changing the internal structure and stress distribution of the polymer layer, which helps to reduce the overall residual stress of the functional current collector. DETAILED DESCRIPTION

[0028] For better understanding and implementation, the technical solution of the present application will be clearly and completely described below in conjunction with embodiments. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments.

[0029] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.

[0030] Unless otherwise indicated, all numerical values ​​expressing quantities of ingredients, reaction conditions, and so forth used in the specification and claims are to be understood as modified by the term “about.” Accordingly, unless indicated to the contrary, the numerical parameters set forth herein are approximations that can vary depending upon the desired properties desired to be obtained.

[0031] As used herein, "and / or" means one or all of the mentioned elements.

[0032] As used herein, “including” and “comprising” encompasses the case where only the stated elements are present as well as the case where there are other elements other than the stated elements.

[0033] All percentages in this application are by weight unless otherwise stated.

[0034] Unless otherwise indicated, "a", "an", "an" and "the" used in this specification are intended to include "at least one" or "one or more". For example, "a component" means one or more components, so more than one component may be considered and may be employed or used in the implementation of the embodiment.

[0035] Example 1 A method for preparing a functional current collector with low residual stress comprises the following steps: S1, electroplating metal layers on the two surfaces of the polymer layer to obtain a finished current collector, and placing the finished current collector at a pressure of 2×10 -3 Pa vacuum atmosphere, nitrogen ion beams were injected into the two surfaces of the above-mentioned current collector product using nitrogen ion implantation equipment (the injection energy of the nitrogen ion beam was 50 keV, the ion beam intensity of the nitrogen ion beam was 5 mA, and the injection dose of the nitrogen ion beam was 5×10 16 Ions / cm 2 ), to obtain a pre-treated current collector; S2, after the injection operation is completed, the pretreated current collector is heat-treated at 80°C for 3 minutes and then cooled to 20°C at a cooling rate of 1°C / min to obtain a functional current collector.

[0036] In the functional current collector, the thickness of the polymer layer (polypropylene film) is 5 μm, the thickness of the metal layer (copper) is 1 μm, and the concentration of nitrogen ions in the interface area accounts for 80% of the total concentration of nitrogen ions in the functional current collector.

[0037] Example 2 A method for preparing a functional current collector with low residual stress comprises the following steps: S1, electroplating metal layers on the two surfaces of the polymer layer to obtain a finished current collector, and placing the finished current collector at a pressure of 9×10 -4Pa vacuum atmosphere, nitrogen ion implantation equipment was used to implant nitrogen ion beams into the two surfaces of the above-mentioned current collector product (the implantation energy of the nitrogen ion beam was 100 keV, the ion beam intensity of the nitrogen ion beam was 15 mA, and the implantation dose of the nitrogen ion beam was 5×10 17 Ions / cm 2 ), to obtain a pre-treated current collector; S2, after the injection operation is completed, the pretreated current collector is heat-treated at 85°C for 4 minutes and then cooled to 20°C at a cooling rate of 2°C / min to obtain the functional current collector.

[0038] In the functional current collector, the thickness of the polymer layer (polypropylene film) is 4 μm, the thickness of the metal layer (copper) is 1.2 μm, and the concentration of nitrogen ions in the interface area accounts for 85% of the total nitrogen ion concentration in the functional current collector.

[0039] Example 3 A method for preparing a functional current collector with low residual stress comprises the following steps: S1, electroplating metal layers on the two surfaces of the polymer layer to obtain a finished current collector, and placing the finished current collector at a pressure of 6×10 -4 Pa vacuum atmosphere, nitrogen ion beams were injected into the two surfaces of the above-mentioned current collector product using nitrogen ion implantation equipment (the injection energy of the nitrogen ion beam was 150 keV, the ion beam intensity of the nitrogen ion beam was 20 mA, and the injection dose of the nitrogen ion beam was 5.5×10 16 Ions / cm 2 ), to obtain a pre-treated current collector; S2, after the injection operation is completed, the pretreated current collector is heat-treated at 90°C for 5 minutes and then cooled to 22°C at a cooling rate of 3°C / min to obtain the functional current collector.

[0040] In the functional current collector, the thickness of the polymer layer (polypropylene film) is 6 μm, the thickness of the metal layer (copper) is 2 μm, and the concentration of nitrogen ions in the interface area accounts for 80% of the total concentration of nitrogen ions in the functional current collector.

[0041] Example 4 The difference between this embodiment and embodiment 1 is that the implantation dose of the nitrogen ion beam in S2 is 5×10 17 ions / cm², and other steps and parameter settings are consistent with Example 1.

[0042] In the functional current collector, the thickness of the polymer layer (polypropylene film) is 5 μm, the thickness of the metal layer (copper) is 1 μm, and the concentration of nitrogen ions in the interface area accounts for 90% of the total concentration of nitrogen ions in the functional current collector.

[0043] Example 5 The difference between this embodiment and embodiment 1 is that in S2, the pretreated current collector is heat-treated at 80°C for 5 minutes and then cooled to 20°C at a cooling rate of 1°C / min to obtain a functional current collector; other steps and parameter settings are consistent with embodiment 1.

[0044] In the functional current collector, the thickness of the polymer layer (polypropylene film) is 5 μm, the thickness of the metal layer (copper) is 1 μm, and the concentration of nitrogen ions in the interface area accounts for 80% of the total concentration of nitrogen ions in the functional current collector.

[0045] Example 6 The difference between this embodiment and embodiment 1 is that in S2, the pretreated current collector is heat-treated at 90°C for 3 minutes and then cooled to 20°C at a cooling rate of 2°C / min to obtain a functional current collector; other steps and parameter settings are consistent with embodiment 1.

[0046] In the functional current collector, the thickness of the polymer layer (polypropylene film) is 5 μm, the thickness of the metal layer (copper) is 1 μm, and the concentration of nitrogen ions in the interface area accounts for 85% of the total concentration of nitrogen ions in the functional current collector.

[0047] Example 7 The difference between this embodiment and embodiment 1 is that the implantation energy of the nitrogen ion beam in S2 is 20 keV, and the other steps and parameter settings are consistent with those in embodiment 1.

[0048] Example 8 The difference between this embodiment and embodiment 1 is that the implantation energy of the nitrogen ion beam in S2 is 200 keV, and the other steps and parameter settings are consistent with those in embodiment 1.

[0049] Example 9 The difference between this embodiment and embodiment 1 is that the ion beam current intensity of the nitrogen ion beam in S2 is 2 mA, and the other steps and parameter settings are consistent with those in embodiment 1.

[0050] Example 10 The difference between this embodiment and embodiment 1 is that the ion beam current intensity of the nitrogen ion beam in S2 is 30 mA, and the other steps and parameter settings are consistent with those in embodiment 1.

[0051] Embodiment 11 The difference between this embodiment and embodiment 1 is that the implantation dose of the nitrogen ion beam in S2 is 5×10 15 ions / cm², and other steps and parameter settings are consistent with Example 1.

[0052] Example 12 The difference between this embodiment and embodiment 1 is that the implantation dose of the nitrogen ion beam in S2 is 5×10 18 ions / cm², and other steps and parameter settings are consistent with Example 1.

[0053] Embodiment 13 The difference between this embodiment and embodiment 1 is that the implantation energy of the nitrogen ion beam in S2 is 150 keV, and the other steps and parameter settings are consistent with those in embodiment 1.

[0054] In the functional current collector, the thickness of the polymer layer (polypropylene film) is 5 μm, the thickness of the metal layer (copper) is 1 μm, and the concentration of nitrogen ions in the interface area accounts for 55% of the total concentration of nitrogen ions in the functional current collector.

[0055] Embodiment 14 The difference between this embodiment and embodiment 1 is that the ion beam current intensity of the nitrogen ion beam in S2 is 20 mA, and the other steps and parameter settings are consistent with those in embodiment 1.

[0056] In the functional current collector, the thickness of the polymer layer (polypropylene film) is 5 μm, the thickness of the metal layer (copper) is 1 μm, and the concentration of nitrogen ions in the interface area accounts for 65% of the total concentration of nitrogen ions in the functional current collector.

[0057] Comparative Example 1 The difference between this comparative example and Example 1 is that the functional current collector does not contain nitrogen ions.

[0058] Test Method 1. Residual stress test The residual stress of the functional current collectors provided in the above embodiments and comparative examples was tested by using a μ-360s X-ray residual stress tester produced by QUANTUM Quantum Scientific Instrument Trading (Beijing) Co., Ltd.

[0059] 2. Adhesion Test The adhesion between the metal layer and the polymer layer in the functional current collectors provided in the above embodiments and comparative examples was tested using an Elcometer 510 automatic pull-off adhesion tester produced by Elcometer Company of the United Kingdom.

[0060] Table 1

[0061] In combination with Examples 1-6, Examples 13-14, Comparative Example 1 and Table 1, it can be seen that in the present solution, by controlling the proportion of the nitrogen ion concentration in the interface between the polymer layer and the metal layer in the total nitrogen ions in the functional current collector, the residual stress in the functional current collector can be eliminated to a great extent, and deformation of the functional current collector or shedding of the surface metal layer can be avoided, which helps to improve the cycle performance and safety performance of the lithium battery.

[0062] In combination with Example 1, Examples 7-8 and Table 1, it can be seen that when the injection energy of the nitrogen ion beam is too low, the nitrogen ions cannot effectively penetrate into the interface between the polymer layer and the metal layer in the functional current collector, which is not conducive to eliminating the residual stress in the functional current collector; when the injection energy of the nitrogen ion beam is too high, although the residual stress in the functional current collector can be eliminated, it may cause structural damage inside the functional current collector, which is not conducive to. On the one hand, excessive injection energy may produce greater impact force and stress on the surface of the material, exceeding the bearing capacity of the material, causing cracks, peeling or other damage to the surface of the material. On the other hand, although the purpose of nitrogen ion implantation is to remove residual stress, if the injection energy is too high, new residual stress may be generated inside the material. These residual stresses may have an adverse effect on the performance and service life of the material.

[0063] In combination with Example 1, Examples 9-10 and Table 1, it can be seen that the ion beam current intensity of the nitrogen ion beam is too low, the operation time for injecting nitrogen ions is too long, and the processing efficiency is low; while the ion beam current intensity of the nitrogen ion beam is too high, it will cause local overheating and surface sputtering, affecting the quality of the metal layer surface and the performance uniformity of each region in the functional current collector.

[0064] In combination with Example 1, Examples 11-12 and Table 1, it can be seen that the implantation dose of the nitrogen ion beam is too low to effectively eliminate the residual stress in the functional current collector; while the implantation dose of the nitrogen ion beam is too high, which may cause serious distortion and a large number of defects in the material lattice in the functional current collector, reduce the hardness and toughness of the functional current collector, and affect the application scope of the functional current collector to a certain extent.

[0065] The above embodiments are only used to illustrate the technical solution of the present application rather than to limit the protection scope of the present application. Although the present application is described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the technical solution of the present application can be modified or equivalently replaced, but these modifications or replacements are all within the protection scope of the present application.

Claims

1. A functional current collector with low residual stress, characterized in that: The functional current collector comprises two metal layers and a polymer layer disposed between the two metal layers; The range from the surface of the polymer layer to the 2-3 μm away from the metal layer in the polymer layer is recorded as region A, and the range from the surface of the metal layer close to the polymer layer to the 100 nm away from the polymer layer in the metal layer is recorded as region B, and the region A and the region B are the boundary regions between the polymer layer and the metal layer; The functional current collector contains nitrogen ions, and the nitrogen ion concentration in the interface area between the polymer layer and the metal layer accounts for more than 80% of the total nitrogen ion concentration in the functional current collector.

2. The functional current collector with low residual stress according to claim 1, characterized in that: The thickness of the polymer layer is 4-6 μm.

3. The functional current collector with low residual stress according to claim 1, characterized in that: The thickness of any one of the metal layers is 1-2 μm.

4. The functional current collector with low residual stress according to claim 2, characterized in that: The polymer layer includes at least one of a polypropylene film, a polyetheretherketone film, a polyphenylene sulfide film, a polyethylene naphthalate film, and a polyimide film.

5. The functional current collector with low residual stress according to claim 3, characterized in that: The metal layer includes any one of copper foil and aluminum foil.

6. The method for preparing a functional current collector with low residual stress according to any one of claims 1 to 5, characterized in that: The steps include: S1, compounding the metal layer on the two surfaces of the polymer layer to obtain a finished current collector, placing the finished current collector in a vacuum atmosphere, and injecting nitrogen ion beams into the surfaces of the two metal layers of the finished current collector to obtain a pretreated current collector; S2, after the injection operation is completed, the pre-treated current collector is subjected to heat preservation treatment and then cooled to obtain the functional current collector.

7. The method for preparing a functional current collector with low residual stress according to claim 6, characterized in that: The pressure of the vacuum atmosphere in S1 is 6×10 -4 -2×10 -3 Pa.

8. The method for preparing a functional current collector with low residual stress according to claim 6, characterized in that: In S1, the metal layer is prepared by magnetron sputtering, electron beam evaporation or laser pulse deposition.

9. The method for preparing a functional current collector with low residual stress according to claim 6, characterized in that: During the implantation operation of S1, the implantation energy of the nitrogen ion beam is 50-150 keV, the ion beam current intensity of the nitrogen ion beam is 5-20 mA, and the implantation dose of the nitrogen ion beam is 5×10 16 -5×10 17 Ions / cm 2 .

10. The method for preparing a functional current collector with low residual stress according to claim 6, characterized in that: In S2, the holding temperature is 80-90°C, the holding time is 3-5min, and the cooling rate is 1-3°C / min, until it cools to 20-25°C.

11. A pole piece, characterized in that: The invention comprises a functional current collector as described in any one of claims 1 to 5 or a functional current collector prepared by the method as described in any one of claims 6 to 10, and an electrode active material located on the functional current collector.

12. A lithium battery cell, characterized in that: Comprising the pole piece as claimed in claim 11.

13. A battery pack, characterized in that: Comprising the lithium battery cell as claimed in claim 12.

14. An electrical equipment, characterized in that: It comprises the lithium battery cell as claimed in claim 12 or the battery pack as claimed in claim 13.

Citation Information

Patent Citations

  • Stainless separator for fuel cell having discontinuous crn surface layer and method for the same

    KR100796526B1

  • A surface treatment method for reactor structure materials

    KR100841083B1

  • Gas barrier structure and method for forming gas barrier structure

    WO2013125351A1

  • Composite current collector, and preparation method therefor and use thereof in lithium-ion battery

    WO2024131980A1